2022
DOI: 10.3390/toxins14030181
|View full text |Cite
|
Sign up to set email alerts
|

Host-Species Variation and Environment Influence Endophyte Symbiosis and Mycotoxin Levels in Chinese Oxytropis Species

Abstract: Oxytropis plants are widely distributed in the grasslands in northern China. Some Oxytropis species have been reported to contain the mycotoxin swainsonine, an alkaloid which causes poisoning in livestock, referred to as locoism. Previous studies showed that endophytic fungi (Alternaria oxytropis) symbiotically associate with these Oxytropis species to produce swainsonine. However, the influence of variation within the Oxytropis genus on the fixation or loss of symbiosis and toxicity is poorly understood, as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…oxytropis, the content of its metabolite swainsonine was also markedly increased (Figure ), which would further affect the health level of livestock due to the toxicity of the alkaloid. Previous studies have shown that the level of swainsonine was related to the abundance of endophytic fungi within the host population . Similarly, the hypothesis that the abundance of endophytic Alternaria was proportional to the content of swainsonine was also supported by the study of Cook et al…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…oxytropis, the content of its metabolite swainsonine was also markedly increased (Figure ), which would further affect the health level of livestock due to the toxicity of the alkaloid. Previous studies have shown that the level of swainsonine was related to the abundance of endophytic fungi within the host population . Similarly, the hypothesis that the abundance of endophytic Alternaria was proportional to the content of swainsonine was also supported by the study of Cook et al…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have shown that the level of swainsonine was related to the abundance of endophytic fungi within the host population. 48 Similarly, the hypothesis that the abundance of endophytic Alternaria was proportional to the content of swainsonine was also supported by the study of Cook et al 9 Integrated multiomics technologies can reveal key cell signaling compounds for plant stress resistance and promote sustainable agricultural production. 49 In this study, swainsonine and apigenin-7-O-glucoside-4-O-rutinoside, metabolic biomarkers screened from pseudotargeted metabolomics, significantly inhibited the growth of pathogenic fungi Leptosphaeria sclerotioides and Colletotrichum americae-borealis by increasing the level of oxidative stress in fungi.…”
Section: ■ Discussionmentioning
confidence: 89%
“…Strain and fermentation culture M. anisopliae (Metarhizium anisopliae (Metsch.) Sorokīn), isolated in the soil, was obtained from Xi'an Jin Berry Biological Technology Co. Ltd., Shaanxi, China andinoculated onto Sabouraud medium (SDA) (Guo et al 2022) and cultured at 28°C for 10 days. Conidiums (1.0×10 7 ) of M. anisopliae were transferred into 300 mL SDA liquid culture medias (without agar) and fermented at 28°C, 180 rpm, for 1-7 d. The fermentation broth was ltered through three layers of Miracloth (EMD Millipore Corp, Billerica, MA, USA) to collect the cultures and the mycelium respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Swainsonine is an indolizidine alkaloid produced by the endophytic fungus Alternaria, and the chemical structure is exhibited in Figure S1. Swainsonine causes neurological disorders in livestock, and several studies have shown that swainsonine can cause liver damage before inducing neurological disorders …”
Section: Introductionmentioning
confidence: 99%